The Influence of Visual Media Indonesia Virtual Tour in Learning Explanatory Text in the Digital Era - Gilang Aulia Prasetya; Murnee Masae; Zahruddin; Maftuhah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research aims to examine the influence of visual media Indonesia Virtual Tour in learning explanatory texts in the digital era at SMP Negeri 3 South Tangerang. In the current era of change, many educational institutions in Indonesia and even outside the country are accustomed to using social media or technology tools to facilitate learning from low level to tertiary level, all of this cannot be separated from social media learning. The author will examine how teachers use the Visual Media Indonesia Virtual Tour tool in learning explanatory texts in the digital era. The method used in this research is a descriptive qualitative approach, qualitative research is research carried out to understand the phenomena experienced by research subjects. Researchers describe all data obtained from interviews, field notes, recordings, etc. that have been carried out and describe each data well in language, not statistical figures. The results of the research show that the way teachers teach through this media is how students respond and motivate them to learn in this era of social media.